USAHA-USAHA PELESTARIAN LINGKUNGAN HIDUP PADA MASYARAKAT BALI KUNO BERDASARKAN REKAMAN PRASASTI - I Ketut Setiawan (Environmental Research Center (PPLH) of Udayana University, 2011)
This study, which is entitled “the attempts done by the old Balinese people to preserve environment’ describes the activities done by the old Balinese people on usual and particular days. As recorded in some epigraphs, preserving environment was one of the activities done. The data obtained from the epigraph, as far as this study is concerned, are classified as the primary data which are supported by the secondary data obtained from relevant studies. Then the data were analyzed, interpreted and synthesized, using inductive and deductive methods. Historical, sociological and archaeological approaches were used to sharpen the analysis and the interpretations made. The results of the analysis show that the people living in the old Bali era voluntarily attempted to preserve their environment to improve their welfare and comfort.